2009
DOI: 10.1002/jcop.20316
|View full text |Cite
|
Sign up to set email alerts
|

Promoting evidence‐based practices: the adoption of a prevention support system in community settings

Abstract: Prevention support systems (PSSs) are designed to help communities implement evidence-based practices (EBPs). Little is known about the factors that influence their adoption. In this article, we examined adoption of a PSS for substance abuse prevention called Getting To Outcomes (GTO) s among staff in two community coalitions with varying levels of exposure to it over a 2-year period. A multistage regression model was used to determine the relative predictive power of organizational, innovationrelated, and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…Third, the AGTO intervention may require more time to stimulate improvements in all areas assessed. This is because AGTO can be complex for community groups, and previous work on the precursor GTO showed that those who perceived GTO as more complex used it less (Hunter et al, 2009). Further, the relationship between TA provider and prevention practitioner—a key driver of change in GTO (Hunter et al, 2009)—takes time to establish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the AGTO intervention may require more time to stimulate improvements in all areas assessed. This is because AGTO can be complex for community groups, and previous work on the precursor GTO showed that those who perceived GTO as more complex used it less (Hunter et al, 2009). Further, the relationship between TA provider and prevention practitioner—a key driver of change in GTO (Hunter et al, 2009)—takes time to establish.…”
Section: Discussionmentioning
confidence: 99%
“…This is because AGTO can be complex for community groups, and previous work on the precursor GTO showed that those who perceived GTO as more complex used it less (Hunter et al, 2009). Further, the relationship between TA provider and prevention practitioner—a key driver of change in GTO (Hunter et al, 2009)—takes time to establish. All three issues were present in a previous smaller study evaluating the precursor GTO intervention (Chinman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Related to the lesson about the importance of relationships to implementation, others have noted that building trust and strong relationships between practitioners (Delivery System) and the TA providers (Support System) helped practitioners take risks associated with engaging in the difficult work needed to improve their prevention practice (Chinman et al 2008; Hunter et al 2009a, b). A strategy to establish trust between TA providers and practitioners that has been helpful to us was to hire “local talent”—i.e., TA providers who have existing relationships with local practitioners and train them in AGTO.…”
Section: Discussionmentioning
confidence: 99%
“…The Fig. 1 The interactive systems framework Prevention Support System serves as the ''bridge'' between the Prevention Synthesis and Translation System and the Prevention Delivery System, providing support to and connecting researchers to practitioners to facilitate bidirectional knowledge transfer (Chinman et al 2008;Flaspohler et al 2008a;Hunter et al 2009). In addition, each of these systems operates within an important macro-system of policy and funding.…”
Section: History and Evolution Of The Partnershipmentioning
confidence: 99%